Building Science Identity Through Mentorship Vision Boards - Andrea Jonahs; Adama Olumo (Canadian Journal for the Scholarship of Teaching and Learning)
This qualitative study describes a novel intervention designed to build science identity in first-year civil engineering students. Science identity is associated with resilience and perseverance in STEM fields, yet practical teaching activities that support science identity are lacking in university classrooms. To address this need, we created a mentorship vision board (MVB) activity that prompted students to locate real people and projects that reflected facets of their identity, values, and interests. Student reflections on their MVBs were analyzed to identify salient themes about how the activity affected their science identity. Findings indicate that students reported greater clarity about who they wanted to be as engineers. By inviting first-year engineering students to see themselves as “engineering people,” the MVB holds the potential to affirm their belonging as students, as professionals, and as future engineers serving their communities.